Clinical features and genetic analysis of Dandy-Walker syndrome - Yanmei Sun; Tao Wang; Ning Zhang; Pingping Zhang; Yali Li (BMC, 2023)
Abstract Background Dandy-Walker syndrome (DWS) is a rare congenital malformation of the central nervous system (CNS), characterized by underdevelopment or dysplasia of the cerebellar vermis, expansion of the fourth ventricle and posterior fossa cistern. The incidence is aboutapproximately 1/25000-1/35000. At present, the etiology and pathogenesis of DWS are not completely clear. It is mostly considered to be a multifactorial genetic disease that is related to both genetic factors and environmental factors. There is no large sample size analysis of the chromosomal profile of DWS up to now. This study aims to provide clinical reference for prenatal diagnosis via summarizing the clinical features and pregnancy outcomes of Dandy-Walker syndrome. Methods A total of 76 cases of foetal Dandy-Walker syndrome out of 19,506 pregnant women underwent cordocentesis or amniocentesis for genetic detection. Rapid prenatal karyotyping, single nucleotide polymorphism array (SNP-array) and BACs-on-Beads™ (BoBs) were performed for prenatal genetic diagnosis. The results of ultrasonography, genetic analysis and pregnancy outcome were recorded. Results Of the 76 cases, 19 were isolated DWS, while 57 cases were accompanied by other ultrasound-visible abnormalities. Ultrasound abnormalities of the CNS were most frequently observed, accompanied by DWS. Twenty-five out of 76 cases had chromosomal abnormalities, and the rate of chromosomal abnormalities increased in pregnant women of advanced maternal age or in combination with other ultrasound abnormalities. Of the 19 cases in the isolated DWS group, nine pregnant women chose to terminate the pregnancy, while seven cases continued the pregnancy and all infants were normal. Among the 57 pregnant women with pathological ultrasound manifestations other than foetal DWS, 44 chose to terminate the pregnancy, while 12 cases continued the pregnancy. Further follow-up revealed one newborn with postnatal neurodevelopmental delay. A female term neonate presented with very severe sensorineural deafness, and an infant died 7 days after birth with abnormal development of multiple organs. Conclusions Pregnant women with DWS in foetal ultrasonic examination should be offered a careful and comprehensive foetal ultrasound scan and further prenatal genetic testing including karyotype analysis and SNP-array. The prognosis of the foetus without chromosomal aberration is good in isolated DWS pregnancies but poor in nonisolated DWS pregnancies.